Novel Malto‐Oligosaccharide‐Producing Amylase AmyAc from Archangium sp. Strain AC19 and Its Catalytic Properties. (23rd June 2021) - Fan, Qiwen; Zhang, Lei; Dong, Chaonan; Zhong, Linli; Fang, Xiaodong; Huan, Minghui; Ye, Xianfeng; Huang, Yan; Li, Zhoukun; Cui, Zhongli
Abstract: Functional maltooligosaccharides (MOSs) derived from starch have potential applications in the food industry and medicine due to their specific functional properties. In this study, a novel maltose (G2) and maltotriose (G3)‐producing amylase AmyAc from Archangium sp. strain AC19 is identified. AmyAc is a protein of 874 amino acids, with an N‐terminal signal peptide as well as hydrolase family 13 (GH13) catalytic and C‐terminal binding modules. However, its sequence is not highly similar to any of the reported starch hydrolases. The V max of AmyAc is 124 µmol min −1 mg −1 under optimal conditions of 50 °C and pH 7.0. AmyAc catalyzes the conversion of MOSs and soluble starch into maltose and maltotriose as the end‐product with more than 85% purity. AmyAc initially produces G2, G3, and oligosaccharides with even units, following by the release of G2 and oligosaccharides with odd units during later stages of hydrolysis, indicating a distinct catalytic selectivity. The production of MOSs from starch by AmyAc is of significant interest due to potential applications in starch processing. Abstract : Maltooligosaccharides (MOSs)‐producing amylases are important tool in the conversion of starch into valuable products. In this study, a novel maltose (G2) and maltotriose (G3)‐producing amylase AmyAc that is able to convert starch into MOSs is identified. Based on the unique hydrolysis, the production of MOSs from starch by AmyAc is of significant interest due to potential applications in starch processing.